Versatility of the Free Anterolateral Thigh Flap for Reconstruction of Soft Tissue Defects - Sarker, Avijit; Islam, Salek Bin; Uddin, Mohammad Nashir; Chowdhury, Ahmedul Kabir; Kalam, Md Abul (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Introduction: Reconstruction of soft tissue defect always poses a reconstructive challenge. The objective of this study was to evaluate the outcome of anterolateral thigh free flap as a versatile flap for soft tissue reconstruction. Methods: In this prospective study carried out in the Department of Plastic Surgery of Dhaka Medical College and Hospital (DMC&H), Dhaka between July 2016 to June 2017, total thirty patients with soft tissue defect in different regions of the body underwent reconstruction of defects with anterolateral thigh free flap. Twenty (60%) patients had defect in lower extremity, seven (23%) in head and neck, two in the trunk, one in upper extremity. The flaps were raised as a standard subfascial flap in 56.67% cases, as suprafascial thin flap in 23% cases and in 20% cases it was raised along with part of vastus lateralis muscle. Results: Out of 30 cases, 73.3% flaps survived completely, 20% patients had total flap loss and 3.3% patients had partial flap loss and another 3.3% had marginal necrosis. Donor site complications were observed in four patients. Conclusions: The study concluded that anterolateral thigh free flap was found to be a reliable option to reconstruct soft tissue defects in different regions of the body with minimal donor site morbidity. J Bangladesh Coll Phys Surg 2025; 43: 109-115